2019
DOI: 10.1111/jcmm.14650
|View full text |Cite
|
Sign up to set email alerts
|

Functions and mechanisms of lysine crotonylation

Abstract: Lysine crotonylation is a newly discovered post‐translational modification, which is structurally and functionally different from the widely studied lysine acetylation. Recent advances in the identification and quantification of lysine crotonylation by mass spectrometry have revealed that non‐histone proteins are frequently crotonylated, implicating it in many biological processes through the regulation of chromatin remodelling, metabolism, cell cycle and cellular organization. In this review, we summarize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 56 publications
1
60
0
2
Order By: Relevance
“…Notably, modifications to isobaric labeling improved its efficiency so that it requires significantly less reagent. The significant reduction in the cost per acquisition make it more likely that TMT will be adopted in clinical tests or patient-specific oncological mapping [52].…”
Section: Advanced Isotope Labeling Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, modifications to isobaric labeling improved its efficiency so that it requires significantly less reagent. The significant reduction in the cost per acquisition make it more likely that TMT will be adopted in clinical tests or patient-specific oncological mapping [52].…”
Section: Advanced Isotope Labeling Strategiesmentioning
confidence: 99%
“…As these advances make PTM-centric experiments easier, efforts to describe the biomedical causes and consequences of protein modifications are increasing. For example, recent applications of PTM-centric mass spectrometry studies include the acetylome effects of deacetylase SIRT5, implicated in maintaining mitochondrial function during acute kidney injury [69]; malonylation and crotonylation have functions in inflammatory signaling [70] and regulation of chromatin remodeling [52], respectively.…”
Section: Post-translational Modificationsmentioning
confidence: 99%
“…Gene Ontology (GO) annotation proteome was derived from the UniProt-GOA The CREBBP and p300 proteins as well as PCAF and MOF catalyze the crotonylation on histones and non-histone proteins 3 . Crotonylation has been demonstrated to be involved transcription and DNA repair 3,4 . Though several proteomic studies have been focused on the regulation of crotonylation in cells [4][5][6] (1.5~2) and Q4 (>2).…”
Section: Bioinformatics Analysismentioning
confidence: 99%
“…These observations support the notion that protein crotonylation may be functionally important for maintaining cell identity in these different culture conditions. In this regard, protein crotonylation is controlled by the balance between writers and erasers [25], whose changes in expression could explain putative differences in crotonylation between the four cell states. However, analysis of the total proteome showed that known crotonylation writers and erasers (also crotonylation readers) do not change noticeably between the four cell states ( Figure S1E).…”
Section: Quantitative Lysine Crotonylome Analysis In Different Pluripmentioning
confidence: 99%